Epidemiology of Respiratory Diseases: Impact on Smallholder Pig Production Systems in Uganda (Pig multipathogen survey and disease impact - Lira district) - Dione, Michel; Oba, Peter; Wieland, Barbara; Ouma, Emily A. (International Livestock Research Institute, 2021)
Knowledge of epidemiology of circulating respiratory pathogens, their impacts on pig productivity and genetic diversity in Uganda is limited or lacking. Thus, identifying circulating pathogens, risk factors for their occurrence and determining their genetic diversity in pig populations in Uganda provides a useful framework for design of prevention and control interventions. In addition, losses associated with respiratory infections need to be quantified to guide decision making processes that aim to reduce the negative impacts of respiratory diseases. This research project is expected to generate important information useful to address critical constraints to pig production and productivity in Uganda. The overall objective of this activity is to determine the impact of respiratory diseases on pig production. The specific objectives are: i. Determine the impact of respiratory diseases on weight gain in pigs ii. Determine the genetic diversity of important respiratory pathogens in domestic pigs in Uganda iii. Quantify economic losses associated with respiratory disease(s)/infections in pigs in Uganda. These data consist of a multi-pathogen baseline study conducted on 259 pigs across 90 farms, 5 rounds of longitudinal monitoring on the same farms for pathogens and economic losses and a cross-sectional pig abattoir survey (3 slabs) in Lira, Uganda.